Numerical Analyses of Single‐Phase Pressure Drop and Forced Convective Heat Transfer Coefficient of Water–Ethanol Mixture: An Application in Cooling of HEV Battery Module. Issue 7 (2nd June 2015) - B.G, Suhas; Sathyabhama, A.
Abstract : The present numerical analyses are related to the cooling of a hybrid electric vehicle (HEV) battery module by water–ethanol mixture. The fluid is passed through a cold plate consisting of two rectangular channels of 0.01 m depth, 0.015 m width, and 0.15 m length. The battery module is represented by a heater placed below the cold plate. The single‐phase pressure drop and single‐phase heat transfer coefficient for water, water–ethanol mixture of mass fraction of 25%, 50%, and 75%, and ethanol are determined numerically for different heat fluxes of 10, 15, 20, and 25 kW/m 2 and different Reynolds numbers 500, 1000, 1500, 2000, and 2500. To solve the Navier–Stokes equation, the pressure correction method was used and to solve the energy equation, the Lax–Wendroff explicit method is used. Numerical results obtained for water are compared with the literature correlations. The friction factor for water deviated by an average of 8.02% from the Lewis and Robertson equation. The Nusselt number for water deviated by 7.35% from the Churchill and Ozoe equation at lower Reynolds number 500 and at higher Reynolds number 2500, Nusselt number deviated by 13.68% from the Stephan equation. The results showed that the heat transfer coefficient increased with an increase in Reynolds number and heat flux. The effect of the increase in Reynolds number is more significant than the increase in heat flux. At higher ethanol mass fraction and higher Reynolds number the heat transfer coefficient increased with heat flux when compared to water. There is no significant decrease in heat transfer coefficient with an increase in ethanol mass fraction. The pressure drop increased and the heat transfer coefficient decreased with an increase in ethanol mass fraction.